Methodological Aspects of Social Preferences Research in the Context of Solving Social Dilemmas - Kovalenko, Alla; Holovina, Albina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article presents an analysis of the main methodological principles and schemes of social preferences experimental research, which are determined as a fundamental concept to understanding the behavior of decision-makers in the process of resolving social dilemmas. The models presented in the article include an analysis of the factors that determine social preferences. Among them are the factors of trust, reliability, reciprocity, rejection of inequality, unconditional altruism and competitive advantage. The article provides a description of the strengths and weaknesses of the classic methods for studying social preferences, which usually take the form of ultimatum game, dictator game, trust game and public goods game. The study reveals the importance of the Nash equilibrium as a way to interpret human behavior in resource allocation during the game. Analysis of numerous literary sources shows that the ultimatum game is a classic scheme for studying the altruistic behavior of people. The submission of a proposal and its acceptance is an example of Nash's ideal equilibrium. Deviation from this balance can be interpreted as altruism. In turn, the trust game is a classic scheme for studying the reciprocity and prosocial orientation. If the behavior of players deviates from Nash's equilibrium, it is interpreted as being caused by trust and reciprocity. The dictator game is a classic scheme for studying the rejection of inequality. The subject's behavior can be interpreted as a rejection of inequality or altruism, but not as a rejection of risk, as the offer of Player 1 is mandatory for Player 2. Public goods game is a classic scheme for studying the competitive orientation. Nash's ideal balance in this form of play is to do nothing for public consumption, but deviating from this rule is interpreted as altruistic behavior that is the opposite of competitive orientation. As a result, the design of psychological research is presented, which most accurately typologies the social preferences of the subjects and can contribute to the creation of a representative model of decision-making process.
Keywords: social preferences; game theory; Nash equilibrium; dictator game; investment game; public goods game; ultimatum game